Academic Procrastination and Its Influence on Mathematics Achievement among Secondary School Students in Pakistan: A Sociocultural Perspective - Sajid Rasheed; Fatima Rasheed; Muhammad Zaman, (Dialogue Social Science Review (DSSR), 2025)
Academic procrastination is a persistent challenge within Pakistani secondary schools, particularly in the context of mathematics education. This study investigates the impact of academic procrastination on students' mathematics achievement, considering sociocultural and familial factors such as parental education, family size, gender, and home study habits. A quantitative survey design was employed, targeting 150 students from public schools in Karachi. Data were analyzed using multiple regression and path analysis techniques. The findings reveal a significant negative correlation between academic procrastination and mathematics performance. Moreover, procrastination levels were influenced by parental education and study hours, suggesting that home environment plays a crucial role. The results underscore the need for targeted interventions to reduce procrastination and improve mathematics learning outcomes in Pakistan. Keywords: Academic procrastination, mathematics achievement, secondary education, parental education, Pakistan, sociocultural factors